2020
DOI: 10.1507/endocrj.ej20-0149
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin induced testicular damage through mitochondria mediated apoptosis, inflammation and oxidative stress in rats: impact of resveratrol

Abstract: The target of this study was to explore the role of mitochondria mediated apoptosis and inflammation in cisplatininduced testicular damage and to evaluate the ameliorative effect of resveratrol. Adult male Wistar rats were randomly allocated to 4 groups. Group I (Control) received normal saline, Group II (Resveratrol) received resveratrol (50 mg/kg/day), Group III (Cisplatin) received cisplatin (7.5 mg/kg/week, i.p.) and Group IV (Resveratrol + Cisplatin) received resveratrol and cisplatin in the same regimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 72 publications
3
21
0
Order By: Relevance
“…Similarly, Aly and Eid (2020) have reported that CP treatment (a single dose of 7.5 mg/kg) increased the activity of Caspase-3 and Bax, while decreased the activity of Bcl-2 in testis. They also showed that resveratrol decreased the activity of Caspase-3 and Bax, but increased the activity of Bcl-2.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Similarly, Aly and Eid (2020) have reported that CP treatment (a single dose of 7.5 mg/kg) increased the activity of Caspase-3 and Bax, while decreased the activity of Bcl-2 in testis. They also showed that resveratrol decreased the activity of Caspase-3 and Bax, but increased the activity of Bcl-2.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have reported that CP (a single dose of 6 mg/kg and 7 mg/kg) causes upregulation of Caspase‐3 and downregulation of Bcl‐2 (Kohsaka et al., 2020; Nna et al., 2020). Similarly, Aly and Eid (2020) have reported that CP treatment (a single dose of 7.5 mg/kg) increased the activity of Caspase‐3 and Bax, while decreased the activity of Bcl‐2 in testis. They also showed that resveratrol decreased the activity of Caspase‐3 and Bax, but increased the activity of Bcl‐2.…”
Section: Discussionmentioning
confidence: 76%
“…The adverse effect on body weight could be probably correlated to its harmfulness on many body systems, and the mechanism may be linked to the generation of free radicals [ 51 ]. With regard to the weight of the testis, it is mainly dependent on the germinal epithelium and the number of germ cells [ 52 , 53 , 54 ]. The significant decline demonstrated after CdCl 2 challenge can be considered an important parameter of toxicity and it may be due to the histopathological damages in the seminiferous tubules (reduced MSTD and Johnsen’s score).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated the protective and therapeutic effects of other substances against different toxics in testes. In particular, Re showed a protective action against testicular toxicity as it upregulated Bcl2, downregulated p53 and Bax gene expression [ 20 , 54 ], and reduced inflammatory cascade [ 54 ]. Furthermore, marked improvements in sperm parameters and histopathological damages were observed in the Re-pretreated mice [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, while paclitaxel significantly increased TNFα, IL-1β and NFκB levels, AM significantly decreased the levels of inflammatory parameters at a dose of 400 mg/kg. In toxicity studies conducted with various chemotherapeutic agents, inflammatory parameters have been shown to increase in testicular tissue (Aly & Eid, 2020;Sherif et al, 2014). To our knowledge, this is the first study to prove a,b,c Differences between the groups (p < 0.05).…”
Section: Discussionmentioning
confidence: 62%